PENGARUH KUALITAS PELAYANAN DAN SUASANA RESTO TERHADAP KEPUTUSAN PEMBELIAN PADA CAFÉ AND RESTO SUGAR RUSH DI BONTANG - Dinda Andriani (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
The research talk about The effect of Services Quality and Store Atmosphere to purchase decision, that has been done service quality and store atmosphere change to purchase decision available at Sugar Rush hasn’t been complete that visitor target.Analysis tool that being used is validity test, reliability test, classic assumption test, multiple regression analysis, F test, T test, and most influence variable test. The result of F test (simultaneous) shows that service quality and store atmosphere significant simultaneously influence to purchase decision. This proved by sig Fvalue = 0,000 < α 0,05. In result of T test (partial) variable service quality significant partially influence to purchase decision, this proved by sig Tvalue = 0,000 < α 0,05 and variable T test result that store atmosphere partially not influence significant with purchase decision, this proved by sig Tvalue = 0,059 > α 0,05. Which most influence is service quality with strandardized coefficients beta value 0,556. This research conclude that service quality and store atmosphere simultaneously significant to purchase decision, as for more effective variabel which is service quality. Advice that can be given to company is add more employee so there’s more clear task and fast service, add additional facility such as wifi and live music and make improvement with parking space and restaurant sign.